The new approach to identification of film reflecting holographic marks - Kostyukevych, S.O.; Muravsky, L.I.; Fitio, V.M.; Voronyak, T.I.; Shepeliavyi, P.E.; Kostyukevych, K.V.; Moskalenko, N.L.; Pogoda, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The new approach for creation of film reflecting holographic marks for optical security is proposed. Such marks are replicas of a reflecting master hologram recorded on a chalcogenide glass layer. To receive the master hologram, the joint power spectrum of a reference phase mask and an input phase mask or a transformed phase mask is produced at the plane of the hologram writing and is modulated by an inclined laser beam. If an inclined laser beam illuminates the replica recorded on a flexible substrate, phase noise including speckle noise is eliminated because the hologram carrier frequency exceeds greatly the limiting frequency of the phase noise power spectrum. Experimental results have shown the principal possibility to produce the high performance film reflecting holographic marks for security applications. The proposed approach can be combined with technologies for fabrication of rainbow holograms. In this case, the received rainbow holograms are the reflecting holographic marks simultaneously. Therefore, they can be verified not only visually, but also by means of automatic identification.